Supraclavicular lymphadenopathy as the initial presentation of metastatic prostate cancer: A case report and review of literature - Chan, Garson (Canadian Medical Association, 2013)
Prostate cancer usually metastasizes to the regional lymph nodes, and distal metastases to supraclavicular lymph nodes are rarely reported, especially as an initial presentation. Limited case reports describe cervical lymphadenopathy as the initial presentation of metastatic prostate cancer, and often with widely disseminated disease. Patients with this initial presentation rarely undergo digital rectal examination or serum prostate-specific antigen (PSA) level measurement as part of their initial investigations. A high index of suspicion is necessary to make the diagnosis of prostate cancer in this clinical setting. We present a rare case of prostate carcinoma presenting with supraclavicular lymph node enlargement at the initial diagnosis. A review of the relevant literature is provided.